Knowledge Management in Organizations 10th International Conference, KMO 2015, Maribor, Slovenia, August 24-28, 2015, Proceedings - Uden, Lorna; Heričko, Marjan; Ting, I-Hsien.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book contains the refereed proceedings of the 10th International Conference on Knowledge Management in Organizations, KMO 2015, held in Maribor, Slovenia, in August 2015. The theme of the conference was "Knowledge Management and Internet of Things." The KMO conference brings together researchers and developers from industry and academia to discuss how knowledge management using big data can improve innovation and competitiveness. The 59 contributions accepted for KMO 2015 were selected from 163 submissions and are organized in topical sections on: knowledge management processes, successful knowledge sharing and knowledge management practices, innovations for competitiveness, knowledge management platforms and tools, social networks and mining techniques, knowledge management and the Internet of Things, knowledge management in health care, and knowledge management in education and research.
Knowledge Management in Organizations – A Bibliometric Analysis of Research Trends -- Unifying Knowledge Creation Process through Cascading Modes of Communication -- The Unspoken Requirements - Eliciting Tacit Knowledge as Building Blocks for Knowledge Management Systems -- Modelling Knowledge Management Processes Using Fuzzy Cognitive Maps -- Performance Measurement of Knowledge Resources Using Fuzzy Logic -- Assessing the Effect of Knowledge Management Initiatives on Stakeholder Objectives Using Fuzzy TOPSIS -- Successful Knowledge Sharing and Knowledge Management Practices -- Heterogeneous Business Process Management: A Metamodel-based Approach -- Application of Knowledge Management for Increasing the Effectiveness of Franchise Based Organizations -- Client-Vendor Knowledge Transfer Mechanisms in the Context of Information Systems Outsourcing -- An Empirical Study of the Effect of SCM Practice on Corporate Performance -- Impact of Knowledge Sharing on Decision Making and Situation Analysis -- Measurement Model of Relationship between Knowledge Management Enablers and Knowledge Management Performance in Public Sector -- A Study on The Influence of National Culture on Knowledge Sharing -- The Relationship between Knowledge Sharing Climate and Conflict Resolution Styles -- Knowledge Sharing and Employee Development in Oil and Gas Companies in the United Arab Emirates -- The Impact of Corporate Social Responsibility on the Firm’s Financial Performance: The Case of Publicly Listed Companies in the United Arab Emirates -- Identification of the Main Problems in the Management of Innovation Processes and the Draft of Appropriate Recommendations -- Innovations for Competitiveness -- Knowledge Management Model for Project Management -- Development of Knowledge Model for Construction Projects -- A Novel Approach to Generating Test Cases with Genetic Programming -- Research about Measurability of Information Quality -- Product Data Analytics Service Model for Manufacturing Company -- Stable Two-Sided Matching of Slot Allocation in Airport Collaborative Decision Making -- Technology Monitoring Systems to Improve the Competitiveness and Innovation in Colombia Companies -- Modelling Knowledge Spillover Effects Using Moderated and Mediation Analysis – The Case of Czech High-Tech Industries -- Indigenous Knowledge and Socioeconomic Development: Indigenous Tourism in Kenya -- Reintegration of Slovak Researchers Returning to Slovak Companies -- Knowledge Management Platforms and Tools -- Possibilities of Streamlining within Business Intelligence Systems in Business Practice -- Framework for Building a Big Data Platform for Publishing Industry -- Cloud Based Office Suites - Users’ Attitudes towards Productivity, Usability and Security -- Component Database Management System Design using Version Control -- Multi-Column Query Method Research and Optimization on HBase -- Social Networks and Mining Techniques -- Introduction to Social Business Process Management -- Understanding a Company’s Social Media Strategies and Customer Engagement -- Using of Text Mining in Online Public Access Catalog -- Learning Ontology from Text: A Storytelling Exploratory Case Study -- State of the Art Construction Based on the J48 Classifier: Case Study of Internet of Things -- Knowledge Management and the Internet of Things -- The Effects of the Internet of Things and Big Data to Organizations and Their Knowledge Management Practices -- Internet of Things Backed by Knowledge Management for Smart Home -- WSN Lifetime Management with the Predictive Energy Management Mechanism for the Autonomous Cooperative Smart Logistics System - A Real World Knowledge Representation Scenario -- A Study on the Effects of LED Light’s Pulse Width Modulation on Work Concentration -- The “Green” in Internet of Things: Case Study of Faculty Environment -- The Research on Path-based DoS Attack Detection Algorithm in Wireless Sensor Networks -- Swarm Intelligence based Data Aggregation for Intruder Detection in Wireless Sensor Networks -- Intelligent Sybil Attack Detection on Abnormal Connectivity Behavior in Mobile Social Networks -- Internet of Things: A Prototype Architecture Using a Raspberry Pi -- Internet of Things for Health: Japanese Consumers’ Needs for Preventive Healthcare Products -- Knowledge Management in Healthcare -- Ontology Driven Personal Health Knowledge Discovery -- Design of Query-Driven Systems for Time-Utility Based Data Mining on Medical Data -- Cord Blood Collection Promotion through Knowledge Sharing Using Change Management HSE model -- Improving Hospital Readmission Prediction Using Domain Knowledge Based Virtual Examples -- Safety Use of Hospital Information Systems: A Preliminary Investigation -- Integration of RIS and PACS for Efficient Knowledge Management in Healthcare – A Case in Slovenia -- Knowledge Management in Education and Research -- Knowledge Management and Intellectual Capital in a University Context -- Social Capital-Knowledge Management (SCKM) Analysis Framework On An E-Portfolio -- Management of Cooperation Activities in University Science Park -- Management Model for Planning Articulation at Universidad Distrital -- Knowledge Ambassadors: Enhancing Tacit Knowledge Transfer in Kenyan Universities -- An Analysis of the Content of Knowledge Management-Related Courses.
Keywords: Information technology; Business—Data processing; Data mining; Artificial intelligence; Application software; IT in Business; Data Mining and Knowledge Discovery; Artificial Intelligence; Computer Appl. in Administrative Data Processing